Effect of probiotics on gut microbiome in patients with administration of surgical antibiotic prophylaxis: A randomized controlled study. Issue 8 (August 2020) - Kaku, Norihito; Matsumoto, Nariyoshi; Sasaki, Daisuke; Tsuda, Keiichi; Kosai, Kosuke; Uno, Naoki; Morinaga, Yoshitomo; Tagami, Atsushi; Adachi, Shinji; Hasegawa, Hiroo; Osaki, Makoto; Yanagihara, Katsunori
Abstract: Surgical antibiotic prophylaxis (SAP) is recommended for the prevention of surgical site infections. However, there is a concern about adverse effects of SAP, such as antibiotic-associated diarrhea (AAD). To prevent AAD, administration of probiotics has been investigated. Although recent advances in next-generation sequencing makes it possible to analyze the gut microbiome, the effect of probiotics on the gut microbiome in the patients with SAP remains unknown. To test a hypothesis that SAP influences the gut microbiome and probiotics prevent the influence, a randomized controlled study was conducted with patients who underwent spinal surgery at Nagasaki University Hospital. After obtaining informed consent, the patients were automatically classified into the non-probiotics group and the probiotics group. In the probiotics group, the patients took 1 g of Enterococcus faecium 129 BIO 3B-R, 3 times a day on postoperative days (PODs) 1–5. The feces of all patients were sampled before administration of SAP and on PODs 5 and 10. We compared alpha and beta diversity and differential abundance analysis of the gut microbiome before and after SAP. During the study period, a total of 33 patients were evaluated, comprising 17 patients in the non-probiotics group and 16 in the probiotics group. There was no significant difference between the groups regarding patient characteristics. In alpha and beta diversity, there were no significant differences among all combinations. In differential abundance analysis at operational taxonomic unit level, Streptococcus gallolyticus and Roseburia were significantly increased in the non-probiotics group and significantly decreased in the probiotics group.